КАТЕRYNOSLAV OR ELYSAVETGRAD REBELLION 1918? GEOGRAPHIC MISHAP VOLODYMYR ANTONOV-OVSEENKO BOOK “NOTES ABOUT CIVILL WAR” (Південний архів (історичні науки), 2021)
The purpose of the work. The article aims to study the problems of Ukrainian Revolution in 1917–1921 on a territory of Kirovograd or Dnipropetrovsk region. The type of article is empirical. An unrenowned episode from the history of Ukrainian Revolution in 1917–1921 is analyzed in the article, in particular, the participation of the citizens of Katerunoslavska province in Kamianske town in the events of “National rebellion” in 1918 in Elysavetgrad against Bolsheviks and anarchists. Results and scientific novelty of the study. The author attracted attention to the geographical mistake in the memoirs of V. Antonov-Ovseenko “Notes About Civil War”. The scientific novelty, that author explaine, that he confused the names of the cities: Katerynoslav and Elysavetgrad. The reasons and consequences of the participation of workers of Dniprovskyi plant in Kamianske city in the events of Elysavetgrad national rebellion are determined in the article on the basis of sources. For a long time Bolsheviks concealed, shifted responsibility to their political opponents and then erased from the pages of censored memoirs of participants of revolutionary events the episode of battles between Kamianske and Elysavetgrad workers because it did not fit into the concept of “class struggle” in the history of revolution in Ukraine. The main result of Kamianske workers deception was the numerous victims on both sides. Only the leaflet spread by Elysavetgrad headquarters of the city protection among Kamianske citizens and the end of battles near Elysavetgrad stopped the following bloodshed. Nevertheless, in their memoirs Bolsheviks from Kamianske continued to accentuate that those were they who had established the Soviet power in Elysavetgrad, continued to be proud of the participation in the attempt of helping Bolsheviks to invade Elysavetgrad. The author originality is refutes these statements on the basis of resources. The material of the article may have practical application in scientific studios on the history of Ukrainian Revolution in 1917–1921 on a territ ory of Kirovograd or Dnipropetrovsk region.
Keywords: revolution, rebellion, bolshevics, anarchists, Red guard, mishap, Katerynoslav, Elysavetgrad, Kamianske.